Factors of using Long-Term Contraception Methods in Reproductive Age Women: Age, Parity, and Husband Support - Susanti Susanti; Mika Tri Kumalaswandari (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2019)
Maternal mortality (MMR) in Cilacap Regency is still high and receives special attention from the District Health Office. One cause of maternal death is 4 Too (too young, too old, too close and too often). Family Planning as one of the government's efforts to reduce MMR. One of the efforts to reduce the use of contraception and the most effective is the Long Term Contraception Method, which has only reached 30%, this is still less than the target so it is necessary to identify family planning participants for the Long Term Contraception Method. The purpose of this study was to determine the relationship of age, parity and husband's support by selecting the Long-Term Contraception Method in the Central Cilacap Health Center. 1. The study design used descriptive analytic with the cross sectional approach, the research sample was taken using purposive sampling method, as many as 99 mothers. Data were analyzed using chi-square test with a significance level of 95% and (0.05). The results of this study indicated age variables (p = 0.398), parity (p = 0.0340, husband's support (p = 0.536), the conclusion of this study was parity related while husband's age and support are not related to the choice of the Long-Term Contraception Method.